PENGEMBANGAN ALAT BLOK PERMAINAN BOLA VOLI - Aprili, Isnani Sara; Supriatna, Eka; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to develop new innovations in the form of volleyball block tools that can help optimize the volleyball block training process and help optimize the results of volleyball smash exercises. This research is a research and development. This research uses the development method of ADDIE with several steps, namely: analysis, design, development, implementation and evaluation. The test subjects in this study were Pontianak City Rajawali club with 26 athletes in total as  samples, 14 female athletes and 12 male athletes. The results of the Volleyball Game Block Tool research are categorized as "Eligible" as  media for volleyball Block training. This can be seen from the results of product validation by media experts with a value of 92.8% and volleyball practitioners with a value of 92.3% and the response of Rajawali club athletes to the developed volleyball. the bok tool also very well seen from the results of the Rajawali club athlete response questionnaire Potianak City 96.9%. So it can be concluded that the volleyball game block tool product is feasible to use to help optimize the results of volleyball smash training.Keywords:  Block Development, Tools Volley